Error estimation and mesh adaptivity for the virtual element method based on recovery by compatibility in patches. (26th June 2020) - D'Altri, Antonio Maria; de Miranda, Stefano; Patruno, Luca; Artioli, Edoardo; Lovadina, Carlo
Summary: In this article, a recovery by compatibility in patches (RCP)‐based a posteriori error estimator is proposed for the virtual element method (VEM), and it is utilized to drive adaptive mesh refinement processes in two‐dimensional elasticity problems. In RCP, recovered stresses are obtained by minimizing the complementary energy of patches of elements over a set of assumed equilibrated stress modes. To this aim, the explicit knowledge of displacements is only needed along the patch boundaries and no knowledge of superconvergent points is required, so making the RCP naturally suitable for the VEM. The a posteriori error estimation is conducted by comparing the stress field of a standard displacement‐based VEM solution and the stress field obtained through RCP. The procedure is simple, and it does not require ad hoc modifications for small patches. The capability of this RCP‐based error estimator to drive adaptive mesh refinements is successfully demonstrated through various numerical examples.